Location, Decentralization, and Knowledge Sources for Innovation - Leiponen, Aija; Helfat, Constance E. (Organization Science, 2011)
When firms seek to innovate, they must decide where to locate their innovation activity. This location choice requires firms to make a simultaneous choice about the organizational structure of innovation activity: almost by definition, multiple locations per firm imply some degree of decentralization. We compare predictions of the knowledge-based view with the predictions of organizational economics regarding the location and decentralization of R&D. Using firm-level data on R&D locations in Finland, we examine the conditions under which firms with multiple R&D locations also have greater innovation output. Our results indicate that multilocation of R&D activity is positively associated with imitative innovation output and is strongly correlated with greater external knowledge sourcing. We also find that the positive association between multiple R&D locations and innovative output does not apply to new-to-the-market innovations. The results are consistent with the interpretation that multilocation of R&D enables firms to access a broad set of external sources of knowledge in pursuit of imitative rather than new-to-the market innovation. Moreover, these findings imply heterogeneity in R&D strategies between firms pursuing new-to-the-market innovation and firms pursuing imitative innovation. It is thus important to distinguish between new-to-the-market and imitative innovations, because their determinants may differ.